The Tradition of Ledug Sura in Islamic Education (Case Study in Magetan District) - Rizqi Rohmah, Kristiana; Aulia Azzahra, Nur; Mufidah Rohmatunnisa, Anaa (ASANKA : Journal of Social Science and Education, 2025)
Globalization has increased the development of various aspects of religious and cultural life in Magetan Regency. The increasing era of globalization is accompanied by the continued advancement of Islamic education, as well as customs that need to be preserved. This research focuses on Javanese customs, specifically the Ledug Sura tradition, during the Islamic New Year celebration, with a particular emphasis on Magetan Regency. The purpose of this research is to determine the importance of religious values in this tradition, which can be incorporated into Islamic education while also respecting the customs that exist within that culture. The method employed is a qualitative case study approach, which involves directly observing this tradition in action. The results of the study indicate that the Ledug Sura tradition serves not only as a means of celebration but also as an important medium for disseminating Islamic educational values among the local community. The impact of the Ledug Sura tradition in Magetan, accompanied by Islamic teachings within it, ensures that the younger generation does not forget their customs and remains committed to their teachings. The conclusion of this research highlights the importance of Islamic teachings in customs, especially in Javanese culture in Magetan Regency, as well as the spread of its traditions.